Islamic microfinance practices and challenges in Malaysia and Palestine - Abdul Razak, Dzuljastri; Mohamad Shafi, Roslina (2013)
Islamic microfinance is relatively new compared to conventional microfinance. Accordingly, new strategies are needed to empower its establishment to prevent the replication of conventional practice. This paper aims to review current microfinance practices in Malaysia and Palestine and to find out its critiques in addressing the needs of the micro entrepreneurs. Furthermore, this paper will also discuss on the characteristics of the Islamic microfinance. It concludes with some solutions to solve the dispute.